Northwest History. Alaska. Earthquakes & Volcanoes. (1937)
Temblors Rock Interior Alaska: Gushers Of Mud And Water Threaten Highway./Last All Day./Windows And Merchandise Bear Brunt Of the Damage, Report. TEMBLORS ROCK INTERIOR ALASKA Gushers Of Mud And Water Threaten Highway. Last All Day. Windows And Merchandise Bear Brunt Of The Damage, Report. By Associated Press. FAIRBANKS, Alaska, July 22. -- Half-dressed men and women hurried from homes and and hotels, frame buildings shook and merchandise tumbled to the floor as a strong earthquake struck Fairbanks and the Alaskan interior early today. The quake began about 7:09 a.m. (9:09 a.m., Pacific standard time). The peak of the first shock lasted more than a minute and tremors were recurrent throughout the day. Seismograph Is Stopped. The second severe shock came at 7:55 a.m. and the third, at 8:01, was so severe it put the north-south motion of the University of Alaska seismograph of commission. Dr. Ervin H. Bramhall, university physicist, said the east-west movement showed a strong epicenter of the quake apparently either southwest or south-southwest. Dr. Bramhall was a scientist with the second Byrd south pole expedition. Motorists arriving later today from the south reported the quake cracked the earth from four to six inches in places along the Richardson highway, forcing up gushers of water and mud from four to six feet high along certain stretches. Suburban and long distance telephone lines were out of service, but it was learned the quake also was felt at Circle, Fort Yukon, Jack Wade, Manley Hot Springs, Tanana and Anchorage. Windows Are Shattered. A survey of damage seemed to show most of it consisted of broken windows and damaged merchandise. Concern was felt for safety of persons in the Black Rapids glacier district near the Big Delta river, about 125 miles southeast of here. Lines were down to the district and it was felt here the area may have been "greatly disturbed." It was recalled that tremors were felt within the last few months there, starting the glacier moving forward rapidly again after it had virtually ceased its advance, which had caused apprehension for the nearby Richardson highway.